Financing costs and the efficiency of public-private partnerships - Besart Avdiu; Alfons J. Weichenrieder (Leibniz Institute for Financial Research SAFE, 2020)
The paper compares provision of public infrastructure via public-private partnerships (PPPs) with provision under government management. Due to soft budget constraints of government management, PPPs exert more effort and therefore have a cost advantage in building infrastructure. At the same time, hard budget constraints for PPPs introduce a bankruptcy risk and bankruptcy costs. Consequently, if bankruptcy costs are high, PPPs may be less efficient than public management, although this does not result from PPPs' higher interest costs.
Keywords: H11; H54; G33; 330; Public-Private Partnerships; Infrastructure; Financing Costs; Default